Manajemen Efektif Pendidik dan Tenaga Kependidikan untuk Menciptakan Pembelajaran yang Berkualitas - Cahyati, Eci; Miranda, Dea; Windasari, Windasari; Cindy, Agustin Hanivia (TSAQOFAH, 2024)
Management of educators and education personnel is a key aspect of personnel management in educational institutions, with strategies for managing teacher and educator staff being the main focus for achieving quality learning. Professional development is also crucial in improving the competence and quality of trainers, while evaluation of their activities is necessary to monitor and improve performance. This study uses the literature method, with data collected through library data, reading, and managing research materials. The findings of this study show that effective human resource management strategies involve careful planning, thorough training and development, and regular performance evaluation. The implementation of education policies that focus on quality learning requires cross-departmental cooperation and active participation from various stakeholders. Environmental and organizational factors, including management, regulation, human resources, infrastructure, relationships, collaboration and changes in the external environment, also influence the effectiveness of HRM in educational institutions. By understanding the importance of educator and education personnel management and implementing effective HRM strategies, educational institutions can create a quality and competitive learning environment. This will positively impact the quality of education provided to students and help achieve broader educational goals.